ACCOUNTABILITY AND PERFORMANCE: EVIDENCE FROM LOCAL GOVERNMENT - Nisriani Manafe, Mesri Welhelmina; Akbar, Rusdi (Journal of Indonesian Economy and Business, 2014)
Â Local government accountability attracts attention since the issuance of the PresidentialInstruction Number 7 of 1999 on Accountability Reporting of the Performance of GovernmentInstitutions (Instruksi Presiden No. 7 Tahun 1999 tentang Laporan Kinerja Instansi Pemerintah).In practice, this accountability is not as was expected. One indication of the causalfactor of the failure of the accountability implementation program is that it is considered as anobligation to describe and to justify the behavior of the accountability actors. The objective ofthis study is to empirically examine the correlation between the requirements of various types ofaccountability with negative perception of the work context and the work performance of theaccountability actors. It contributes to the empirical evidence for the correlation among thevarious types of accountability obligation and the work performance based on the institutionaltheory with mixed method, which is a quantitative approach with PLS and a qualitativeapproach with thematic analysis. Its samples are 201 SKPD officers in the local government ofNusa Tenggara TimurProvince. The results of the study show that the conflict in theaccountability requirement has significant impact on the work context with negative perceptionat different levels, but does not have any significant impact on the work performance of theaccountability actors.Keywords: accountability, accountability requirements, work performance, and mixed method.